PELAKSANAAN PENYELIDIKAN DAN PENYIDIKAN PERKARA PIDANA OLEH KEPOLISIAN TERHADAP LAPORAN MASYARAKAT DI POLISI SEKTOR LIMA PULUH - Afrialdo, Masrizal; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Implementation of inquiries and investigations guided by the provisions laid down in the Criminal Procedure Code and Law No. 2 in 2002. The duties and authority of the police has been arranged therein, one of the police authority to perform its obligations is to receive reports or complaints from anyone about the crime. But in fact, many people report about a crime that is not in the process and ignored by the police especially those of the Police Sector Fifty although it is clear that the report is a crime, it makes society into doubt and criticizing the performance of the Police Sector Fifty impressed lazily in their duties. The purpose of this thesis, namely: First, to investigate the implementation of the conduct of investigations and the investigation of criminal matters by police reports from the public sector police Fifty Second, to determine the obstacles in the implementation of the examination and investigation of criminal matters by police reports from the public sector police Fifty third, To know the efforts made to overcome the obstacles in the conduct of investigations and the investigation of criminal cases by police reports from the public sector police Fifty.This type of research is classified in socio-juridical research, because this research author directly conduct research on a study in order to provide a complete and clear picture of the issues examined. This research was conducted in the Police Sector Fifty, while the sample population is the whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interviews and assessment literature.From the results, it can be concluded that, First, implementation of the examination and investigation of criminal matters by police reports from the public sector police Fifty have not been implemented optimally and benyak as opposed to termination procedures set out in the Criminal Code investigation. Second, constraints in the implementation of the examination and investigation of criminal matters by police reports from the public sector police Fifty among others; The absence of expert crime scene in Police Sector Fifty, the insufficient police officers in terms of quantity, and the lack of budgetary support for the handling of criminal cases. Third, efforts are being made to overcome the obstacles in the implementation of the examination and investigation of criminal matters by police reports from the public sector police Fifty namely, providing expert crime scene in Police Sector Fifty, adding members of the investigator or recruit investigators aide in handling criminal offenses and prepare plan requirements for the handling of criminal acts.Keywords: Research and Investigation-Crime-Community Reports